Fashion in the Fairy Tale Tradition What Cinderella Wore - Do Rozario, Rebecca-Anne C. (Springer International Publishing, 2018)
This book is a journey through the fairy-tale wardrobe, explaining how the mercurial nature of fashion has shaped and transformed the Western fairy-tale tradition. Many of fairy tale's most iconic images are items of dress: the glass slippers, the red capes, the gowns shining like the sun, and the red shoes. The material cultures from which these items have been conjured reveal the histories of patronage, political intrigue, class privilege, and sexual politics behind the most famous fairy tales. The book not only reveals the sartorial truths behind Cinderella's lost slippers, but reveals the networks of female power woven into fairy tale itself.